2019
DOI: 10.2147/ott.s196322
|View full text |Cite
|
Sign up to set email alerts
|

<p>The role of miR-382-5p in glioma cell proliferation, migration and invasion</p>

Abstract: Background: Dysregulation of a single miRNA can play an essential role in tumor development and progression. Recent studies have shown that miR-382-5p can function as an oncogene or as a tumor suppressor in different types of cancers. However, the role of miR-382-5p in glioma growth and expansion has not been characterized. Methods: Quantitative real time-PCR (qRT-PCR) was used to measure miR-382-5p levels in glioma tissues. The miR-382-5p mimics and inhibitors were employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…37,47 Studies have reported that YB1 can regulate proliferation and metastasis by binding to lncRNAs 37,47 or miRNAs, 48 and even demonstrate that YB1 effects EMT. 37,47 Studies have reported that YB1 can regulate proliferation and metastasis by binding to lncRNAs 37,47 or miRNAs, 48 and even demonstrate that YB1 effects EMT.…”
Section: Discussionmentioning
confidence: 99%
“…37,47 Studies have reported that YB1 can regulate proliferation and metastasis by binding to lncRNAs 37,47 or miRNAs, 48 and even demonstrate that YB1 effects EMT. 37,47 Studies have reported that YB1 can regulate proliferation and metastasis by binding to lncRNAs 37,47 or miRNAs, 48 and even demonstrate that YB1 effects EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR‐940 inhibits glioma progression both in vitro and in vivo by targeting CKS1 . Furthermore, miR‐382‐5p expression was found to be reduced in glioma tissues, and its overexpression inhibits glioma cell proliferation, migration, invasion and epithelial–mesenchymal transition by targeting Y box‐binding protein 1 …”
Section: Discussionmentioning
confidence: 99%
“…The mature gene locus were chr14:101,054,316-101,054,337, and the base sequence was GAAGUUGUUCGUGGUGGAUUCG , with a length of 22 nt. (Fig.1) 2.1.2 hsa-miR-382-5P participates in disease regulation Using PubMed to retrieve the related literature of miR-382-5P, we found that miR-382-5P was upregulated in acute promyelocytic leukemia [7,8] , atherosclerosis [12] ,breast cancer [4] ,epidural fibrosis [10] , primary myelofibrosis [9] , primary liver cancer [11] ,cervical cancer [13] , but down-regulated in glioma [5,6] ,oral squamous cell carcinoma [3] ,miR-382 was down-regulated in non-small cell lung cancer [14,15] , osteosarcoma [16] , prostate cancer [19] ,ovarian cancer [20] , primary liver cancer [24] , colorectal cancer [21,22] , while schizophrenia [25] ,diabetic nephropathy [17] , IgA nephropathy [18] ,infantile hemangioma [23] . Thus, the expression of miR-382-5P is tissue-specific, and it is involved in the regulation of cell viability, migration, invasion, angiogenesis, proliferation, cell differentiation, oxidative stress and other biological behaviors.…”
Section: Data Analysis Of Tcga Databasementioning
confidence: 99%
“…A series of nucleases obtained mature miR-382-5P and miR-382-3P by cutting and editing miR-382, in which miR-382-5P was located in the long arm of chromosome 14. In recent years, many studies have shown that the expression of miR-382-5P is abnormal in oral squamous cell carcinoma [3] ,breast cancer [4] ,glioma [5,6] ,acute promyelocytic leukemia [7,8] ,primary myelofibrosis [9] ,epidural fibrosis [10] ,primary liver cancer [11] ,atherosclerosis [12] ,cervical cancer [13] ,miR-382 is abnormal in non-small cell lung cancer [14,15] , osteosarcoma [16] , diabetic nephropathy [17] , IgA nephropathy [18] prostate cancer [19] ,ovarian cacner [20] ,colorectal cancer [21,22] ,infantile hemangioma [23] ,primary liver cancer [24] ,schizophrenia [25] , which are closely related to the proliferation, differentiation, migration, invasion, drug resistance and other biological processes of tumor cells. However, the expression and clinical significance of miR-382-5P in ovarian cancer have not been reported.…”
Section: Introductionmentioning
confidence: 99%